Maldives : 2007 Article IV Consultation-Public Information Notice; Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report ;, 2019)
This 2005 Article IV Consultation with Maldives discusses that Maldives has rebounded strongly from the tsunami of late 2004. Gross domestic product has grown rapidly, underpinned by a robust increase in tourist arrivals, and by construction activity pertaining to the development of new resorts. Inflation remains low although it is on a rising trend. The exchange rate peg continues to serve the country well. The main challenge for Maldives is to ensure that favorable growth prospects are not undermined by fiscal excesses and consequent macroeconomic instability. The IMF staff urged the authorities to prioritize expenditures in line with more realistic revenue estimates, so as to achieve the stated objective of zero domestic financing of the budget. There has been a recent increase in debt ratios due to construction of new resorts and the government's ambitious infrastructure program. The new central bank act has separated the positions of finance minister and governor of the central bank and reorganized the governing body of the central bank. Going forward it will be important to entrench central bank independence.